RANCANGAN PROTOTYPE APLIKASI LAUNDRYTIME MENGGUNAKAN METODE UCD - Liontadinda Ayu Amizhora; Tata Sutabri (CV. ADIBA AISHA AMIRA, 2023)
UI (User Interface) is the process of displaying a result in the form of a display that can be seen by the user. Meanwhile, UX (User Experience) is the process of displaying a result in the form of a display that can be seen by the user. Because both are very important, starting from UX which determines that the application can be run comfortably, and UI plays a role in deciding the appearance to make it more attractive. This article describes an application called laundrytime that can make it easier for users to pick up and order laundry through the application. By using the UCD method we can find out what users want exactly. This UCD method has four stages, namely Understand Context of Use, Specify User Requirements, Design Solutions and Evaluation Againts Requirements which get the final result, namely the prototype.